The effects of 12-week psyllium fibre supplementation or healthy diet on blood pressure and arterial stiffness in overweight and obese individuals. - Pal, Sebely; Khossousi, Alireza; Binns, Colin; Dhaliwal, Satvinder; Radavelli-Bagatini, Simone (Cambridge University Press, 2012)
Endothelial dysfunction and increased arterial stiffness occur early in the pathogenesis of the metabolic syndrome and they are both powerful independent predictors of cardiovascular risk. A high-fibre diet has been correlated with lower BMI and a lower incidence of hyperlipidaemia, CVD, hypertension and diabetes. The present randomised, parallel-design study compared the effects of fibre intake from a healthy diet v. fibre supplement diets on blood pressure (BP) and vascular function over 12 weeks. Overweight and obese adults were randomised to one of three groups: control (with placebo), fibre supplement (FIB) or healthy eating group with placebo (HLT). Systolic blood pressure (SBP) was lower in the FIB group compared with the control group at week 6, but not at week 12. However, SBP was lower in the HLT group compared with control group at week 12. At week 6, the FIB group presented lower diastolic blood pressure and augmentation index compared with the control group, but this result did not persist to the end of the study. The present study did not show any improvements in BP or vascular function in overweight and obese individuals with psyllium fibre supplementation over 12 weeks of intervention. However, a healthy diet provided the greatest improvements in BP in overweight and obese subjects. Further research with hypertensive individuals is necessary to elucidate whether increased fibre consumption in the form of psyllium supplementation may provide a safe and acceptable means to reduce BP, vascular function and the risk of developing CVD.